Responses of different community user groups to biodiversity conservation of protected areas in lowland fynbos : the case of the Wolfgat Nature Reserve - Manuel, Theodore Llewellyn (Department of Biological Sciences, 2014)
Includes bibliographical references (p. 245-269).